O-046 Reproductive prospects for ICSI children. (30th June 2022) - Belva, F; Hes, F; Tournaye, H; Bonduelle, M; Liebaers, I; Verheyen, G; Van Steirteghem, A
Abstract: Intracytoplasmic sperm injection (ICSI), developed 30 years ago in our Center, allowed men with low to extremely low sperm quality to become the genetic father of their child. Overall, ICSI is now applied in up to 70% of all ART cycles and has resulted in the birth of millions of children worldwide. ICSI circumvents natural sperm selection mechanisms and concerns related to transgenerational inheritance of male infertility following ICSI could not be fully answered till today, given the young age of the offspring born after ICSI. Since genetic abnormalities account for one third of all cases of male factor infertility, it is essential to identify these genetic abnormalities because of the potential risk of their transmission to the offspring through the use of ART. As ICSI is nowadays performed even in couples with normal semen parameters, the disentanglement of procedure-related and parental background-related factors on the health of the offspring is important. Due to the safety concerns regarding the health of children born after ART, a longitudinal follow-up program was set up in our Center in the 80's, resulting in data of more than 50 000 pregnancies. To date, more than 25 000 children are conceived after ICSI in our Center. We have not only the worldwide eldest cohort of ICSI offspring but also a uniform cohort of children and young adults conceived by ICSI because of (severe) male factor infertility. We present the results of these prospective studies with focus on the reproductive health in ICSI children between 8 and 22 years and compare these with available data from others. First of all, we will show data on the gonadal function assessed both clinically and by means of biomarkers at pre-pubertal and pubertal ages in ICSI boys. Secondly, we will present findings on the reproductive status of young adult men and women conceived after ICSI between 1992 and 1996: results of hormonal work-up, physical examination and semen parameters for ICSI men and results of hormone levels and antral follicle counts for ICSI women. Finally, we will discuss the findings in these cohorts of children and young adults conceived because of male infertility in view of the available literature regarding reproductive function in offspring conceived following ICSI.